Admissibility of illegally obtained e-evidence: A critical study of EU law and the precedents of the European Court of Human Rights - Oleksii Volodymyrovych Kostenko; Vahid Akefi Ghaziani (European Journal of Privacy Law & Technologies)
Whether illegally obtained evidence should be deemed inadmissible is a question that many jurisdictions still struggle with. In this regard, there is no internationally accepted standard that orients national jurisdictions in detaching valid from invalid evidence. This study focuses on the two-fold legal systems practiced within EU law and that of the European Court of Human Rights in order to identify their points of disagreement and to approximate the two systems. The outcomes suggest that the GDPR has not provided any balancing guidance for inconsistent fundamental rights; therefore, EU member states have wide discretion in prevailing one right over another. Despite this, aiming to protect EU fundamental rights, particularly the right to protection of personal data (Article 8 of the EU Charter) and the fairness procedure of a trial (Article 47 of the Charter), national courts, in the absence of domestic guidelines, are welcomed and urged to follow the ten-factor test of the judgment Beuze v. Belgium (ECHR, November 8, 2018). Finally, after examining the court's guidance, the paper at hand partially changes the test and offers a more reliable test to reconcile privacy rights with the right to a fair trial. This test could serve as a yardstick for national courts as well as upcoming ECtHR precedent.